2013
DOI: 10.4236/jbbs.2013.33033
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects of Malathion Exposure on Recognition Memory and Spatial Learning in Males Wistar Rats

Abstract: Most cognitive effects of Organophosphate Pesticides (OP) are induced after exposure to parathion, chlorpyrifos and diazinon, which the usage Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Another study of developmental toxicity to Malathion also demonstrated a low body weight gain in young rats at stage (GD 6-PND 45) [21]. From a pathophysiological point of view, the low body weight gain in the exposed groups could be explained by the effect of overexpression of ACh molecules which increases gastric motility and decreases intestinal absorption [22].…”
Section: Systemic Effects Of Chronic Exposure To Dimethoatementioning
confidence: 99%
See 3 more Smart Citations
“…Another study of developmental toxicity to Malathion also demonstrated a low body weight gain in young rats at stage (GD 6-PND 45) [21]. From a pathophysiological point of view, the low body weight gain in the exposed groups could be explained by the effect of overexpression of ACh molecules which increases gastric motility and decreases intestinal absorption [22].…”
Section: Systemic Effects Of Chronic Exposure To Dimethoatementioning
confidence: 99%
“…The long-term developmental exposure (GD 6-PND 45) to Malathion induced a very significant inhibition of AChE associated with altered locomotors activity and high anxiety behavior [21], [27].…”
Section: Effects Of Dimethoate On Locomotors and Exploratory Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Another study of the developmental toxicity in Malathion also demonstrates a low physical weight gain for young rats to the (GD 6-PND 45) stage [16]. From the physio-pathological point of view, the low physical weight gain of the exposed groups could be attributed to the effect of overexpression of the ACh molecules which increases the gastric motility and decreases the intestinal absorption [17].…”
Section: Effect Of Dimethoate On Body Weightmentioning
confidence: 99%